2013
DOI: 10.1186/1475-2875-12-247
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and molecular study of artesunate + sulphadoxine-pyrimethamine in three districts of central and eastern India

Abstract: BackgroundArtesunate + sulphadoxine-pyrimethamine (AS + SP) is recommended throughout India as the first-line treatment for uncomplicated falciparum malaria. Due to the presence of several eco-epidemiological zones of malaria and variable drug pressure, it is necessary to evaluate the efficacy of this combination in different regions of India. The objective of this study was to use clinical and molecular methods to monitor the efficacy of AS + SP in three diverse sites.MethodsThe study was undertaken in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Although a study in DRC reported a conservative prevalence of 60% (23) at 59R, other studies found slightly higher prevalence (87%-98%) at this codon (10,21,22,24,26,29), compared to 78% demonstrated in this study. In agreement with our study, investigations elsewhere found a prevalence of ≥97% at 108N (10,(21)(22)(23)(24)26,27,29). In contrast to average prevalence (66%-68%) reported in India and Gabon (24,26), prevalence of >90% at PfDHPS437G was reported in this study, western Kenya and parts of central Africa.…”
Section: Iptp-sp Is An Important Prophylactic Therapy Recommended Forsupporting
confidence: 92%
See 1 more Smart Citation
“…Although a study in DRC reported a conservative prevalence of 60% (23) at 59R, other studies found slightly higher prevalence (87%-98%) at this codon (10,21,22,24,26,29), compared to 78% demonstrated in this study. In agreement with our study, investigations elsewhere found a prevalence of ≥97% at 108N (10,(21)(22)(23)(24)26,27,29). In contrast to average prevalence (66%-68%) reported in India and Gabon (24,26), prevalence of >90% at PfDHPS437G was reported in this study, western Kenya and parts of central Africa.…”
Section: Iptp-sp Is An Important Prophylactic Therapy Recommended Forsupporting
confidence: 92%
“…Studies elsewhere have documented quadruple mutations (65%) in Equatorial Guinea (22) and 48% in DRC (23), and triple mutations (92%) in Gabon (24) and 61-71% in Burkina Faso (25) as the most prevalent. Similar to India, where double mutation was the most prevalent (26,27), a study in Brazil reported double mutation as most prevalent but did not find quintuple or quadruple mutations (28).…”
Section: Iptp-sp Is An Important Prophylactic Therapy Recommended Formentioning
confidence: 76%
“…This is important, as treatment in case of failure to the antimalarial CQ and SP has now become very common in almost all malaria endemic regions of the globe including India (Cui et al, 2015; Klein, 2013). In Odisha, high level of resistance to both CQ and SP has been reported from many malarious districts including Keonjhar, Sundargarh, Anugul and Sambalpur districts (Mohanty et al, 2009; Peterson et al, 1988; Srivastava et al, 2013; Sutar et al, 2011), with no report from the Deogarh district.…”
Section: Introductionmentioning
confidence: 99%
“…A single mutation in pfdhfr or pfdhps gene is not enough to cause treatment failure and multiple mutation combinations in these two genes were associated with failure of SP as anti-malarial therapy [ 15 , 16 ]. Various parts of India reported single, double, triple and quadruple mutant pfdhfr gene [ 17 22 ]. However, double mutation at codon 59 and 108 in pfdhfr gene was predominant throughout India [ 17 22 ].…”
Section: Introductionmentioning
confidence: 99%